The effects of traffic accidents on pregnancy: Is hospitalization necessary in every case? - DENİZBAŞI ALTINOK, ARZU; TEMÜRLENK, ASLI TUĞÇE; SOYSAL, DİDEM; ÇEVİK, MERAL; SOYSAL, SUAH; PEKİN, TANJU (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2020)
BACKGROUND: This study aimed to show whether it is necessary to hospitalize pregnant women who have been involved in traffic accidents. METHODS: Patients at a hospital in Istanbul, Turkey, who underwent traffic accidents between 2012 and 2018 were studied, and pregnant patients' files were evaluated. Demographic and obstetric features of patients, type of accident, type of trauma, Glasgow Coma Score, whether or not hospitalization were examined, the response of patients to hospitalization, and the obstetric and maternal results of accidents were assessed. RESULTS: In the present study, 95 patients were included. Overall, hospitalization was recommended for 50 patients, but of these, 58% refused to be admitted. No patients who refused hospitalization had complications. Preterm labor was seen in 3.2% of patients, while 3.2% had a fetal loss and 5.3% had a placental abruption. Only one mother was lost (1.1%) due to sustaining multiple traumas in a traffic accident. Hospitalization was increasingly indicated with increasing gestational age, but other parameters had no effect on hospitalization. CONCLUSION: The likelihood that hospitalization was recommended for pregnant women involved in traffic accidents increased with gestational age. Patients with minor trauma who refused hospitalization had no complications.
Keywords: Hospitalization; pregnancy; traffic accidents; MINOR TRAUMA; WASHINGTON-STATE; OUTCOMES